2016
DOI: 10.1017/s0033291716001525
|View full text |Cite
|
Sign up to set email alerts
|

Most of the genetic covariation between major depressive and alcohol use disorders is explained by trait measures of negative emotionality and behavioral control

Abstract: BackgroundMental health disorders commonly co-occur, even between conceptually distinct syndromes, such as internalizing and externalizing disorders. The current study investigated whether phenotypic, genetic, and environmental variance in negative emotionality and behavioral control account for the covariation between major depressive disorder (MDD) and alcohol use disorder (AUD).MethodA total of 3623 members of a national twin registry were administered structured diagnostic telephone interviews that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
(84 reference statements)
0
15
0
Order By: Relevance
“…However, adjustment for MDD did not abolish our association suggesting that this shared liability may be more general than MDD (e.g. Ellingson et al, 2016). Third, increased likelihood of substance use disorders in those with a prior history of SA may reflect a general predisposition towards impulsive and aggressive behaviors (Turecki, 2005).…”
Section: Discussionmentioning
confidence: 64%
“…However, adjustment for MDD did not abolish our association suggesting that this shared liability may be more general than MDD (e.g. Ellingson et al, 2016). Third, increased likelihood of substance use disorders in those with a prior history of SA may reflect a general predisposition towards impulsive and aggressive behaviors (Turecki, 2005).…”
Section: Discussionmentioning
confidence: 64%
“…However, our results do not provide support for the evidence of a stronger association between depressive symptoms and alcohol use among people with lower SES, but rather indicate that the SES impact on mental disorders is controversial which may vary between countries [19] and the types of measurements used for either depressive and alcohol use disorders or SES variables [31]. The signi cant relationship between MDE and AUD could be explained in terms of shared common genetic and environmental factors in the comorbidity of depressive disorder and AUD, as investigated in other studies [34][35][36]. It could also be explained in terms of causality where depressed persons may turn to alcohol as self-medication for their symptoms and develop AUD afterwards [37].…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, the latest theoretical models predict that depression shares a common potential endophenotype, or reward dysfunction, with the impulsivity-based disorders including substance abuse, which is substantiated by accumulating physiological grounds 3841). Also, a large-scale twin study reported that the genetic covariation between depression and AUD could be explained by negative emotionality and behavioral control 42). In other studies, it was demonstrated that insulin-like growth factor-1 (IGF-1) was significantly higher in patients with AUD accompanied with depressive symptoms than ones without the symptoms, which shows IGF-1 would be a biomarker of AUD accompanied with depression 43).…”
Section: Discussionmentioning
confidence: 99%